The West Palaearctic Dineura species, focussing on Sweden (Hymenoptera, Tenthredinidae) - Liston, Andrew; Prous, Marko; Vårdal, Hege (Zootaxa, 2019)
Four Dineura species are now considered to occur in the West Palaearctic, including northern Europe, but D. parcivalvis has not been found in Scandinavia. Dineura pullior Schmidt & Walter, 1995 is treated as a new junior subjective synonym of D. virididorsata (Retzius, 1783). An illustrated key to adults is presented. Lectotypes are designated for seven nominal taxa: Dineura stilata var. virilis Enslin, 1918, Dineura testaceipes var. nigriventris Enslin, 1915, Dineura virididorsata var. dorsalis Enslin, 1915, Nematus posticus Förster, 1854, Nematus xanthocerus Hartig, 1840, Nematus xanthopus Zaddach, 1876, and Tenthredo (Allantus) stilata Klug, 1816. Distributions in the Fennoscandian countries are outlined, with particular reference to Sweden.